THE NORTHERN HEROES OF THE CONTEMPORARY WORLD ARCHITECTURE - Dr Sagdic (STEF92 TECHNOLOGY LTD, 2014)
From an architectural office, that was founded to become the antidote to the star-architecture, here there are three herotic names on the cat walk of the contemporary architecture; Rem Koolhaas, as the founder of OMA, Winy Maas as the founder of MVRDV and finally Bijark Ingles as the founder of BIG. The beginning of 1990's is the time of the capital market changes the hand by the neo-liberalism; inter connected networks, known generally as the internet, start to be called as internet, which will be the new space of human relations without sensations but with digital senses. As culturally, the rise of the multiculturalism is started and thus, alternative media is born. Finally the capitalist free market economy moves toward adopting elements of western culture to the vast points of the world. And Zit is seen that a new life style, which pushes up to the other corners of the world by USA, is started to take the rest under its' effects. These years are the years of having many names of star-architects on the praxis field. So, what makes Rem Koolhaas and the other two names from his office different than these names on the field? It is known that, Rem Koolhaas has been causing trouble in the world of architecture since his student days in London in the early 1970s, and his habit of shaking up established conventions has made him one of the most influential architects of his generation. Winy Maas and his Dutch firm MVRDV and Bjarke Ingels and his Copenhagen-based firm BIG are disproportionate number of the profession's rising stars. It is for sure that these two architects dig through Koolhaas' books and looking for his ideas. It seems that the attraction lies, in part, in his ability to keep everyone off balance. Unlike other architects of his stature, such as Frank Gehry or Zaha Hadid, who have continued to refine their singular aesthetic visions over long careers, his works like a conceptual artist-able to draw on a seemingly endless reservoir of ideas, even spreading to his pupils and their firms and their architectural styles, as well. Thus, the paper will have the true story of three northern heroes of the Contemporary World Architecture, as discussing their characteristic sides on their most popular projects.
Keywords: Reem Koolhaas; Winy Maas; Bijark Ingles; comtemporary architecture; Arts & Humanities - Other Topics